Hydraulic stowing - A solution for subsidence due to underground mining in the USA - Kausik M. Sinha (International Conference on Ground Control in Mining, 1989)
Hydraulic stowing, which is being practiced in several major coal producing countries to deal with adverse mining conditions, usually permits almost 100% coal recovery from underground mines with minimal and controlled surface subsidence. It can be implemented in the US coal mines to reduce the severe effect of land subsidence and at the same time improve the cost of coal production, both of which are major setbacks for the coal industry in the USA